Impact of Depression and Anxiety on Health During Covid-19 Pandemic: Understanding the Impact of Depression and Anxiety on Health in the Elderly during the Covid-19 Pandemic (Journal of Advances and Scholarly Researches in Allied Education, 2021)
It is common for geriatric mental health to be underestimated, and for the elderly's difficulties tobe considered normal. Because of their lower levels of knowledge and lack of access to correctinformation about the outbreak of the pandemic elderly population was found to be both terrified anddismissive of warnings. As a result of changes in job structure, career possibilities, and demographics,many older adults are increasingly living alone while their children and grandchildren work and reside invarious cities or countries. As we learn more about social isolation and the dynamics of socialrelationships under stress, loneliness, and how to create cost-effective pandemic managementstrategies, this urgent problem becomes even more important to us. Anxiety of getting the sickness andlosing loved ones exacerbates an already terrible situation, making it much more challenging.Depression, anxiety, and stress are increasingly well recognised symptoms among understudies.Although it is difficult to distinguish between them, it is critical to diagnose and treat infections sincethey are linked to fundamental suffering and death.